2020
DOI: 10.3390/ijms21124397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SOX2 Repression on Corneal Endothelial Cells

Abstract: Purpose: Human corneal endothelial cells (hCECs) pump out water from the stroma and maintain the clarity of the cornea. The sex-determining region Y-box 2 (SOX2) participates in differentiation during the development of the anterior segment of the eye and is found in the periphery of wounded corneas. This study was performed to investigate the effect of SOX2 repression on hCECs. Methods: Cultured hCECs were transfected by siRNA for SOX2. The wound healing rate and cell viability were measured. The cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…SOX2 plays a critical role in eye development, participating in differentiation during the development of the AS. 43,44 It closely interacts with PAX6 during early lens development, and SOX2 expression level has been detected in the developing lens vesicle of human embryos. 26,43 This transcription factor also plays a crucial role in NCC formation that is essential in AS development.…”
Section: Discussionmentioning
confidence: 99%
“…SOX2 plays a critical role in eye development, participating in differentiation during the development of the AS. 43,44 It closely interacts with PAX6 during early lens development, and SOX2 expression level has been detected in the developing lens vesicle of human embryos. 26,43 This transcription factor also plays a crucial role in NCC formation that is essential in AS development.…”
Section: Discussionmentioning
confidence: 99%
“…RMST works this way in neurons, where it promotes neurogenic differentiation of stem cells by interacting with the transcription factor SOX2 to co-regulate a large pool of downstream genes that are essential for neurogenesis ( Ng et al, 2013 ). Whether this is the case in ECs is unclear, as little is known about the functional roles of SOX2 in ECs, although one study has shown that SOX2 knockdown attenuates survival, proliferation, and migration in corneal ECs due to downregulation of cyclin D1 and CDK1 and upregulation of CDKN2A, a cell cycle inhibitor ( Hwang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cells (1 × 10 4 ) per well were seeded in a 96-well plate and treated with miRNA for 48–72 h. Cell viability was evaluated using a cell counting kit-8 (CCK-8; Dojindo, Kumamoto) [ 73 ]. After incubation with CCK-8 solution for 1–2 h, a Synergy HTX (BioTEK, Winooski, VT) multi-mode reader was used for evaluating cell viability by measuring optical density (OD) at 450 nm [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells (1 × 10 4 ) per well were seeded in a 96-well plate and treated with miRNA for 48–72 h. Cell viability was evaluated using a cell counting kit-8 (CCK-8; Dojindo, Kumamoto) [ 73 ]. After incubation with CCK-8 solution for 1–2 h, a Synergy HTX (BioTEK, Winooski, VT) multi-mode reader was used for evaluating cell viability by measuring optical density (OD) at 450 nm [ 73 ]. A bromodeoxyuridine (BrdU) incorporation assay kit (Roche Diagnostics, GmbH, Mannheim, Germany) was employed for evaluating cell proliferation rate according to manufacturer’s protocol [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation